2014
DOI: 10.1021/jf404832s
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Chardonnay Grape Seed Flour Reduces Plasma Cholesterol Concentration, Hepatic Steatosis, and Abdominal Fat Content in High-Fat Diet-Induced Obese Hamsters

Abstract: The mechanisms for the hypocholesterolemic and antiobesity effects of grape seed flours derived from white and red winemaking processing were investigated using male Golden Syrian hamsters fed high-fat (HF) diets supplemented with 10% partially defatted grape seed flours from Chardonnay (ChrSd), Cabernet Sauvignon (CabSd), or Syrah (SyrSd) pomace as compared to a HF control diet for 3 weeks. Hamsters fed the ChrSd diet had significantly lowered plasma total-, VLDL-, and LDL-cholesterol concentrations compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 32 publications
7
44
2
Order By: Relevance
“…We previously showed that hypocholesterolemic and hypolipidemic effects of ChrSd supplementation of Golden Syrian hamsters on a HF and hypercholesterolemic diet are associated with altered hepatic expression of genes related to bile acid, cholesterol, and lipid metabolism [9]. In the current study, exon microarray analysis identified differentially expressed hepatic genes in DIO mice, providing novel biological insights into the effects of ChrSd supplementation on HF diet-induced hepatic steatosis.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We previously showed that hypocholesterolemic and hypolipidemic effects of ChrSd supplementation of Golden Syrian hamsters on a HF and hypercholesterolemic diet are associated with altered hepatic expression of genes related to bile acid, cholesterol, and lipid metabolism [9]. In the current study, exon microarray analysis identified differentially expressed hepatic genes in DIO mice, providing novel biological insights into the effects of ChrSd supplementation on HF diet-induced hepatic steatosis.…”
Section: Discussionmentioning
confidence: 65%
“…Catechin inhibited lipid accumulation in HepG2 cells and mouse liver [5,6]. Supplementation with catechin-rich grape seed extract and catechin-rich Chardonnay grape seed flour (ChrSd) upregulated expression of genes related to fatty acid oxidation and downregulated genes related to fatty acid synthesis in liver [79], resulting in reduced hepatic steatosis. An extract from the pomace of the red American grape Norton induced anti-inflammatory effects in mice fed a high-fat (HF) diet and exhibited in vitro antioxidant activity [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, GSPE has shown an ability to reduce hepatic lipid accumulation in the presence of a high‐fat cafeteria diet . The hepatoprotective effects of grape seed extracts against increased lipogenesis and hepatic lipid accumulation on a high‐fat diet have also been demonstrated in several other in vivo studies . Finally, grape seed extracts have demonstrated hepatoprotective effects in humans with steatosis, as GSE (2000 mg/day for 3 months) improved the grade of steatosis in these patients and reduced serum levels of the liver enzyme alanine aminotransferase (ALT), an indicator of liver damage…”
Section: Grape Seed Procyanidin Extractmentioning
confidence: 99%
“…In similar animal models, supplementation with grape pomace or aqueous extracts counteracted adiposity, inflammation, liver damage and impaired insulin signaling associated with metabolic syndrome [94]. Hypocholesterolemic and anti-obesity effects of grape seed flours from white and red winemaking processing were described on high-fat fed hamsters [95]. …”
Section: Main Applications Of Phenol-based Polymers In Food and Hementioning
confidence: 99%